Calidad de vida y estrés laboral en los docentes de la Facultad de Ciencias Sociales de la Universidad Técnica de Machala en el periódo 2014 - 2015. - Oviedo Reyes, María José (2015)
The development of this thesis entitled " Quality of life and work stress on teachers of the Faculty of Social Sciences at the Technical University of Machala in the period 2014 - 2015 " is a research project aimed at determining the relationship between quality life and work stress, in order to check if being subjected to high stress levels affect the quality of life in teaching .